Predicting the effect of environmental humidity on COVID-19 trend in Medan, Indonesia - Tri Bayu Purnama (Social Medicine Publication Group, 2021)
Objectives: This study aims to estimate effect of environment humidity on COVID-19 in Indonesia. Design: This study used ecological study to investigate time series of environment parameters and COVID-19 data. Spearman correlation test was applied to analyzed the correlation. Setting: This study located in Medan, Indonesia which was the largest city in Western part of Indonesia. Participants: COVID-19 cases as the outcome of this study which was obtained from department of health in Medan. Temperature, humidity, duration of sun exposure was used as environmental parameters. Results: Humidity has detected as positive correlation with COVID-19 and temperature has shown as negative correlation. There is no significant different on environmental data before and after COVID-19 detected in Medan. Conclusions: Predicting trend of environment parameters and COVID-19 is needed to conduct public health preparedness of COVID-19 strategy.